Business plan for business development and financing opportunities for (micro) small and medium enterprises - Juwita, Ratna; Sari, Mia Andika; Ingriyani, Lini; Maris, Anis Wahyu Intan; Warsini, Sabar; Aminah, Indianik (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2024)
One of the problems faced by MSMEs is the difficulty of obtaining capital from outside parties. After conducting interviews with the Bogor Regency MSME association which accommodates about 700,000 MSMEs, information was obtained that one of the causes of the funding difficulties was the unavailability of a business plan by MSMEs. This was also confirmed through answers from MSMEs trainees, where 100% of MSMEs did not have a written business plan either manually or digitally. The method for community development activities is Participatory Action Research (PAR), which emphasizes meeting needs and solving problems in the community. The Business Model Canvas method was chosen for making MSMEs' business plan by reviewing the literature and paying attention to best practices. After attending the training, all MSMEs understand the Business Model Canvas (BMC). After understanding BMC, all MSMEs created business models in groups with assistance from community engagement team (authors). MSMEs fill all blocks relatively well in BMC, but there needs to be an increase in filling customer segments and cost structure. Next, the business model created by the MSME is input into a digital application, which is ready to be printed by the MSME (carried out in the next activity). It is hoped that this business model in digital and print form will answer one of the administrative obstacles in obtaining external funding.